Réponses

2013-05-28T18:28:17+02:00

1. a- (x+2)(x+3)

         = x*x + x*3 + 2*x + 2*3

         = x² + 3x + 2x + 6

         = x² + 5x + 6

    b- (x+5)(7+x)

         = x*7 + x*x + 5*7 + 5*x

         = 7x + x² + 35 + 5x

         = x² + 12x + 35

 

2. a- pour x=0

         0² + 5*0 + 6

        = 0 + 0 + 6

        = 6

        pour x=1:

         1² + 5*1 + 6

        = 1 +5 +6

        = 12

 

    b. pour x=0

        0² + 12*0 +35

       = 0 + 0 + 35

       = 35

       pour x=1

       1² + 12*1 +35

      = 1 + 12 +35

      = 48

 

ET VOILA!!